Urogenital trichomoniasis in women: state-of-the-art and treatment issues - O.I. Letyaieva; O.R. Ziganshin (LCC «Medicine-Inform», 2019)
Urogenital trichomoniasis in women: state-of-the-art and treatment issues O.I. Letyaeva, O.R. Ziganshin South Ural State Medical University, Chelyabinsk, Russian Federation Currently, sexually transmitted infections (STIs) and urogenital infections are an important clinical, epidemiological, and pharmacoeconomic issue of public health. Urogenital trichomoniasis is the most common STI caused by Trichomonas vaginalis, flagellar parasite which affects human urogenital tract. In 10% to 50% of patients with trichomoniasis infection is asymptomatic. In women, major complications of trichomoniasis are pelvic inflammatory disease (i.e.m salpingoophoritis, endometritis, pelviperitonitis, cystitis, and pyelonephritis) and unfavorable effects on the pregnancy and its outcomes. 5-nitroimidazols are the only approved drug class for urogenital trichomoniasis. Aim: To compare clinical microbiological efficacy of metronidazole and ornidazole for urogenital trichomoniasis in women. Patients and Methods: 47 women aged 19-42 years with urogenital trichomoniasis were enrolled in this short-term open prospective randomized strudy. All patients were subdivided into two groups. 23 women (group I) received metronidazole 500 mg twice a day for 7 days. 24 women (group II) received ornidazole 500 mg twice a day for 5 days. Control group included 25 healthy women. Native smear microscopy, PCR, and ELISA were applied. Results: Before treatment, all women reported on complaints of foul-smelling vaginal discharge, genital burning and itching. Clinical laboratory signs of inflammation, deep suppression of residential lactoflora, and significant increase in pro-inflammatory cytokine levels in vaginal discharge were revealed. Conclusions: ornidazole 500 mg twice a day for 5 days has demonstrated high efficacy and safety for urogenital trichomoniasis in women of reproductive age. This medication provides more significant decrease in pro-inflammatory cytokine levels in vaginal discharge and do not suppress resident vaginal flora. Keywords: Trichomonas vaginalis, urogenital trichomoniasis, proinflammatory cytokines, lactoflora, treatment, diagnosis, ornidazole, metronidazole. For citation: Letyaeva O.I., Ziganshin O.R. Urogenital trichomoniasis in women: state-of-the-art and treatment issues. Russian Journal of Woman and Child Health. 2019;2(2):126-130.